Effect of Discovery Learning on Student’s Achievement in Acid-Base Chemistry - Herman, Mimi; Putri, Naya Eliya; Sari, Dwivelia Aftika (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study aimed to determine the effect of the Discovery Learning model on students’ learning outcomes in acid-base material at SMAN 1 Sungai Tarab. The research employed a quasi experimental method using a nonequivalent control group design. The sample consisted of 45 students selected through a total sampling technique. Data were collected through observation, documentation, and learning achievement tests. The findings showed that students who learned through the Discovery Learning model achieved higher learning outcomes than those who received conventional instruction. Hypothesis testing indicated that the implementation of the Discovery Learning model had a significant effect on students’ learning outcomes in acid-base material. These findings suggest that Discovery Learning can be used as an effective instructional alternative to enhance students’ engagement and conceptual understanding in chemistry learning, particularly in acid-base topics.